Electrode material, preparation method thereof and sodium ion battery

By doping metal nitrides in hard carbon materials and forming closed pores, the problem of low sodium storage utilization rate in hard carbon materials during pore storage is solved, and the effect of improving the sodium storage capacity performance of electrode materials is achieved.

CN119833594AActive Publication Date: 2025-04-15SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202411885678.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-15
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

In the prior art, during the pore sodium storage process of hard carbon materials, sodium is mainly concentrated in the pore wall area, resulting in a low utilization rate of sodium storage in the pore center area, affecting the capacity performance of hard carbon sodium storage.

Method used

An electrode material is used, which comprises a carbon matrix and a metal nitride doped in the carbon matrix, with a closed pore at least a portion of the metal nitride located in the closed pore. Through pre-carbonization treatment, pore formation treatment, metal salt solution impregnation and high-temperature sintering, metal nitride-modified electrode materials were prepared.

Benefits of technology

The capacity performance of the electrode material's sodium storage capacity is improved, the electric field and storage activity in the central area of ​​the closed pore is enhanced, polarization and sodium evolution are reduced, and the utilization rate of sodium storage is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833594A_ABST
    Figure CN119833594A_ABST
Patent Text Reader

Abstract

The invention provides an electrode material, a preparation method thereof and a sodium ion battery. The electrode material comprises a carbon substrate and metal nitride doped in the carbon substrate, the carbon matrix has a closed hole in which at least a portion of the metal nitride is located. The carbon substrate is provided with the closed hole, at least part of the metal nitride is filled in the closed hole, the closed hole can prevent the metal nitride from escaping from the hole, the metal nitride in the closed hole can improve the electric field and the sodium storage activity of the central area of the closed hole, the internal resistance of sodium filled in the closed hole is reduced, polarization is inhibited, and sodium precipitation is reduced; the sodium storage utilization rate of the central area of the closed hole is improved, and the sodium storage capacity performance of the electrode material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Sodium-ion batteries have the characteristics of high safety, fast charging, and low temperature resistance. They can be used in combination with lithium-ion batteries and even replace lithium-ion batteries in some application fields. The raw materials of hard carbon materials are cheap, easy to obtain, and renewable. They have the advantages of high capacity, high rate, and long life when used as sodium negative electrodes. At present, one of the keys to improving the energy density of sodium-ion batteries lies in improving the capacity performance of hard carbon materials.

[0003] In the related technology, the capacity performance of hard carbon materials is generally improved by pore creation; however, in the process of pore sodium storage, sodium is mainly concentrated in the pore wall area, while the electric field in the center of the pore is weak and the sodium storage activity is low, and sodium cannot be further filled, resulting in a low sodium storage utilization rate in the center of the pore, which affects the capacity performance of hard carbon sodium storage. Summary of the invention

[0004] The embodiments of the present invention provide an electrode material and a preparation method thereof and a sodium ion battery, which can improve the technical problem of poor capacity performance of hard carbon sodium storage.

[0005] In a first aspect, an embodiment of the present invention provides an electrode material, comprising

[0006] a carbon matrix having closed pores;

[0007] A metal nitride, wherein the metal nitride is doped in the carbon matrix;

[0008] Wherein, at least part of the metal nitride is located in the closed pores.

[0009] In one embodiment, the metal nitride includes any one or more of iron nitride, cobalt nitride, nickel nitride, copper nitride, vanadium nitride, titanium nitride, manganese nitride, and zirconium nitride; and / or

[0010] The mass percentage of the metal nitride in the closed pores in the electrode material is 0.35%-2.2%; and / or

[0011] The mass percentage of the metal nitride in the electrode material is 0.5%-3.0%; and / or

[0012] The particle size of the metal nitride is less than 1 μm, preferably, the particle size of the metal nitride is less than 500 nm; further preferably, the particle size of the metal nitride is less than 100 nm; and / or

[0013] At least part of the metal nitride is doped on the surface of the carbon matrix; and / or

[0014] The carbon matrix includes a porous hard carbon layer and a carbon coating layer coated on the surface of the porous hard carbon layer.

[0015] In one embodiment, the particle porosity of the electrode material is 5%-35%, preferably, the particle porosity is 10%-25%; and / or

[0016] The conductivity of the electrode material is 40S / cm-70S / cm; preferably, the conductivity is 46S / cm-65S / cm; further preferably, the conductivity is 50S / cm-60S / cm; and / or

[0017] The carbon interlayer spacing of the electrode material is 0.37nm-0.39nm; and / or

[0018] The median particle size of the electrode material is 3 μm-15 μm; and / or

[0019] The specific surface area of ​​the electrode material is 2.0 m 2 / g-10.0m 2 / g.

[0020] In a second aspect, an embodiment of the present invention provides a method for preparing the electrode material as described above, the method comprising the following steps:

[0021] Pre-carbonizing the carbon source to obtain a pre-carbonized material;

[0022] Performing pore-forming treatment on the pre-carbonized material and crushing it to obtain a first precursor;

[0023] impregnating the first precursor in a metal salt solution to obtain an intermediate;

[0024] reacting the intermediate with a process gas at a high temperature to obtain a second precursor;

[0025] The second precursor is sintered at high temperature to obtain the electrode material.

[0026] In one embodiment, the carbon source includes any one or more combinations of plant carbon sources, sugar carbon sources, resin carbon sources, and polymer carbon sources; and / or

[0027] The temperature of the pre-carbonization treatment is 450°C-650°C; and / or

[0028] The pre-carbonization treatment time is 0.5h-24h; and / or

[0029] The pre-carbonization treatment is carried out in an inert gas atmosphere or an oxygen-deficient atmosphere, wherein the inert gas atmosphere includes any one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere or a krypton atmosphere or a combination of at least two thereof, and the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content ≤1wt%.

[0030] In one embodiment, in the solid phase pore formation, the temperature of the high temperature treatment is 600° C.-800° C., and the time of the high temperature treatment is 0.5 h-8 h; and / or

[0031] The mass ratio of the pre-carbonized material to the solid phase pore forming agent is 1:(0.4-3.0); and / or

[0032] The solid phase pore forming agent comprises at least one of sodium hydroxide, potassium hydroxide, sodium oxide, potassium oxide, sodium carbonate, potassium carbonate, potassium bicarbonate, sodium bicarbonate, calcium oxide and zinc chloride; and / or

[0033] In the solid phase pore formation, the inert atmosphere includes any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two thereof; and / or

[0034] The solid-phase pore-forming treatment also includes a solid-phase pore-forming modified material purification treatment, which includes: mixing the solid-phase pore-forming modified material, acid solution, and pure water in a mass ratio of 1: (0.5-2): (2-5) and stirring for 0.5h-24h, performing solid-liquid separation after the stirring is completed, washing the purified product obtained by solid-liquid separation to a pH of 2.5-4.5, and drying, wherein the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid; and / or

[0035] In the gas phase pore formation, the first temperature is 800° C.-1000° C., and the holding time is 1 h-8 h; and / or

[0036] The pore-forming gas includes any one of water vapor, carbon dioxide, chlorine, oxygen, ozone, and air, or a combination of at least two thereof; and / or

[0037] The gas-phase pore-forming treatment also includes a gas-phase pore-forming modified material purification treatment, which includes: mixing the gas-phase pore-forming modified material, acid solution, and pure water according to 1: (0.5-2): (1.2-5) and stirring for 0.5h-24h, performing solid-liquid separation after stirring, washing the purified product obtained by solid-liquid separation to a pH of 4-8, and drying, wherein the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid.

[0038] In one embodiment, the step of immersing the first precursor in a metal salt solution to obtain an intermediate specifically includes:

[0039] The first precursor is immersed in the metal salt solution, stirred for 3h-24h, separated from the solid and liquid, and dried to obtain the intermediate.

[0040] In one embodiment, the concentration of the metal salt solution is 0.5wt%-5wt%, and the mass ratio of the first precursor to the metal salt solution is 1:(3-20); and / or

[0041] The median particle size of the first precursor is 3 μm-15 μm; and / or

[0042] The metal salt includes a soluble salt of Co, Ni, Cu, V, Ti, Mn, Fe or Zr, and the soluble salt includes one or a combination of at least two of sulfate, nitrate and chloride.

[0043] In one embodiment, the step of reacting the intermediate with a process gas at a high temperature to obtain a second precursor specifically includes:

[0044] Under inert atmosphere conditions, the intermediate is placed in a reaction furnace, a process gas is introduced, the temperature is raised to a second temperature, the temperature is maintained, and the second precursor is obtained by cooling.

[0045] In one embodiment, the second temperature is 1000° C.-1400° C., and the holding time is 3 h-10 h; and / or

[0046] The process gas is one of ammonia, methylamine, ethylamine, diethylamine, n-propylamine, isopropylamine, or a combination of at least two of them. Preferably, the selected process gas includes at least one of methylamine, ethylamine, diethylamine, n-propylamine, and isopropylamine; and / or

[0047] The inert atmosphere includes any one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere or a krypton atmosphere, or a combination of at least two of them.

[0048] In one embodiment, in the step of sintering the second precursor at high temperature to obtain the electrode material, the high temperature sintering is performed under inert atmosphere conditions, and / or the temperature of the high temperature sintering is 1200° C.-1500° C., and the time of the high temperature sintering is 0.5 h-10 h; and / or

[0049] Before the second precursor is subjected to high temperature sintering, the method further includes the following steps: uniformly mixing the coated carbon source and the second precursor.

[0050] In one embodiment, the mass ratio of the second precursor to the coated carbon source is 1:(0.01-0.1); and / or

[0051] The coated carbon source comprises any one or more combinations of asphalt, sucrose, phenolic resin, polyacrylic resin, glucose, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyvinyl alcohol, epoxy resin, urea-formaldehyde resin, and melamine resin; and / or

[0052] The inert atmosphere is any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two of them.

[0053] In a third aspect, an embodiment of the present invention provides an electrode plate, comprising the electrode material as described above or the electrode material prepared by the preparation method as described above.

[0054] In a fourth aspect, an embodiment of the present invention provides a sodium ion battery, comprising the electrode material as described above or the electrode material prepared by the preparation method as described above.

[0055] Beneficial effects of the embodiments of the present invention:

[0056] In an embodiment of the present invention, the electrode material includes a carbon matrix and a metal nitride doped in the carbon matrix, the carbon matrix has closed pores, and at least part of the metal nitride is located in the closed pores. On the one hand, the metal nitride has high stability, is not easy to have side reactions with other components in the battery, and is not easy to decompose under the action of the electric field; in addition, the metal nitride has a high electronic conductivity characteristic, and the metal nitride is doped in the carbon matrix, which can increase the overall electronic conductivity of the carbon matrix. On the other hand, the carbon matrix has closed pores, and the closed pores are filled with metal nitrides. The closed pores can limit the escape of the metal nitride from the pores. The metal nitride in the closed pores can increase the electric field and storage activity in the central area of ​​the closed pores, reduce the internal resistance of the closed pores filled with sodium, inhibit polarization, reduce sodium precipitation, and improve the utilization rate of sodium storage in the central area of ​​the closed pores, thereby improving the sodium storage capacity performance of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] In order to more clearly illustrate the solutions in the present application or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0058] Figure 1 A preparation flow chart of an embodiment of the electrode material provided in this application;

[0059] Figure 2This is a SEM image of the electrode material prepared in Example 1 of the present application;

[0060] Figure 3 The first charge and discharge curves of the electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 4 provided in this application;

[0061] Figure 4 This is a room temperature 1C / 1C@500 cycle performance curve of the electrode material prepared in Example 1 provided in the present application. DETAILED DESCRIPTION

[0062] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the drawings; while "inside" and "outside" refer to the outline of the device.

[0063] In the related technology, the capacity performance of hard carbon sodium storage is poor and needs to be further improved.

[0064] To solve the above problems, an embodiment of the present application provides an electrode material, which includes a carbon matrix and a metal nitride doped in the carbon matrix; the carbon matrix has closed pores, and at least part of the metal nitride is located in the closed pores.

[0065] The closed pores are incompletely closed pores with gaps, through which sodium ions can enter and exit the closed pores, and at the same time, the metal nitride in the solid state in the closed pores cannot overflow the closed pores through the gaps. The formation of the gaps is not limited, and the gaps can be formed by interlayer spacing between carbon layers, or by structures such as gaps and channels on the carbon matrix that are connected to the closed pores.

[0066] In this embodiment, on the one hand, the metal nitride has high stability and is not easy to react with other components in the battery; in addition, the metal nitride has high electronic conductivity characteristics, and the carbon matrix is ​​doped with metal nitrides, which can increase the overall electronic conductivity of the carbon matrix. On the other hand, the carbon matrix has closed pores, which are filled with metal nitrides. The closed pores can limit the escape of the metal nitrides from the pores. In addition, the metal nitrides in the closed pores can increase the electric field and storage activity in the central area of ​​the closed pores, reduce the internal resistance of the closed pores filled with sodium, inhibit polarization, reduce sodium precipitation, and improve the utilization rate of sodium storage in the central area of ​​the closed pores, thereby improving the capacity performance of the electrode material for sodium storage.

[0067] In one embodiment, the metal nitride includes any one or more combinations of iron nitride, cobalt nitride, nickel nitride, copper nitride, vanadium nitride, titanium nitride, manganese nitride, and zirconium nitride.

[0068] In one embodiment, the mass percentage of the metal nitride in the electrode material is 0.5%-3%. Optionally, the mass percentage of the metal nitride in the electrode material can be any one of 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, etc. or a range between any two of them, which is not limited here.

[0069] In one embodiment, the mass percentage of the metal nitride in the closed pores in the electrode material is 0.35%-2.2%; optionally, the mass percentage of the metal nitride in the closed pores in the electrode material can be any one of 0.35%, 0.6%, 1.0%, 1.4%, 1.8%, 2.0%, 2.2%, etc., or a range between any two of them, which is not limited here. In this embodiment, if the content of the metal nitride in the closed pores is too little, it is easy to cause the content of the metal nitride distributed in the closed pore area of ​​the electrode material to be insufficient or missing, thereby causing the closed pore sodium storage activity of the electrode material to decrease, the utilization rate of sodium storage in the closed pore area to be low, and the internal resistance of the diffusion of sodium ions in the pore area to increase, thereby causing the capacity performance, rate performance and cycle performance of the electrode material to decrease; if the content of the metal nitride in the closed pores is too high, it is easy to cause the metal nitride to occupy too much closed pore volume, reduce the closed pore volume that can be used for sodium storage, and cause the capacity performance of the electrode material to decrease.

[0070] In one embodiment, the particle size of the metal nitride is less than 1 μm, preferably, the particle size of the metal nitride is less than 500 nm; further preferably, the particle size of the metal nitride is less than 100 nm. The smaller the particle size of the metal nitride, the wider the distribution of the metal nitride on the surface and closed pore area of ​​the electrode material, which is convenient for improving the contact degree between the metal nitride and the carbon matrix, better modifying the modification site, better reducing the diffusion internal resistance of sodium ions on the surface and closed pore area of ​​the electrode material, reducing the polarization of the electrode material, improving the uniformity of the current and voltage distribution of the electrode material during the charge and discharge process, and further improving the capacity performance, rate performance and cycle performance of the electrode material.

[0071] In one embodiment, at least part of the metal nitride is doped on the surface of the carbon matrix. In this embodiment, the metal nitride on the surface of the carbon matrix can improve the electronic conductivity of the carbon matrix surface, reduce the contact internal resistance between carbon matrix particles, inhibit polarization, reduce sodium precipitation, and improve the rate performance and cycle performance of the carbon matrix.

[0072] In one embodiment, the carbon matrix includes porous hard carbon and a carbon coating layer coated on the surface of the porous hard carbon. In this embodiment, the carbon coating layer can convert the open pores in the porous hard carbon into closed pores with sodium storage activity, increase the number of closed pores, and at the same time, facilitate the fixation of metal nitrides in the closed pores.

[0073] In one embodiment, the particle porosity of the electrode material is 5%-35%, preferably, the particle porosity is 10%-25%. In this embodiment, the particle porosity of the electrode material can be any one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, etc. or a range between any two, which is not limited here. In this embodiment, if the particle porosity is too large, it is easy to cause the pores in the carbon matrix to be too large, and the effect of forming closed pores through processes such as carbon coating and high-temperature sintering is not ideal; if the particle porosity is too small, it is easy to cause the pore volume in the carbon matrix to be too small, and the volume of closed pores formed through processes such as carbon coating and high-temperature sintering is too small, the capacity of pore sodium storage is reduced, and the effect of improving the capacity performance of the electrode material is not ideal.

[0074] In one embodiment, the conductivity of the electrode material is 40S / cm-70S / cm; preferably, the conductivity is 46S / cm-65S / cm; further preferably, the conductivity is 50S / cm-60S / cm. In this embodiment, the conductivity of the electrode material can be any one of 40S / cm, 45S / cm, 50S / cm, 55S / cm, 60S / cm, 65S / cm, 70S / cm, etc. or a range between any two, which is not limited here. In this embodiment, if the conductivity is too low, the internal resistance of sodium ion migration of the electrode material increases and the kinetic performance decays; if the conductivity is too high, more metal nitrides are required to modify the electrode material, which easily causes waste of the pore volume of the electrode material and reduces the capacity performance.

[0075] In one embodiment, the carbon layer spacing of the electrode material is 0.37nm-0.39nm; in this embodiment, the carbon layer spacing of the electrode material can be any one of 0.37nm, 0.375nm, 0.38nm, 0.385nm, 0.39nm, etc. or a range between any two of them, and is not limited here.

[0076] In one embodiment, the median particle size of the electrode material is 3μm-15μm; optionally, the median particle size of the electrode material can be any one of 3μm, 6μm, 9μm, 11μm, 13μm, 15μm, etc. or a range between any two, which is not limited here. In this embodiment, if the median particle size of the electrode material is too small, it is easy to cause the specific surface area of ​​the electrode material to be too high, reducing the first efficiency of the battery; in addition, if the median particle size of the electrode material is too small, more binders are required in the process of making the negative electrode sheet, and too much binder is easy to cause the power performance of the battery to decrease; if the median particle size of the electrode material is too large, the particle gap of the electrode material increases, which is easy to cause the compaction density of the negative electrode sheet to be low, and the distance for the sodium ions to diffuse from the surface of the electrode material particles to the center of the electrode material particles is too large, and the dynamic performance is reduced. In addition, the edges and corners of the large-particle electrode material are sharper, and it is easy to pierce the current collector when making the negative electrode sheet, resulting in a decrease in the yield rate.

[0077] In one embodiment, the specific surface area of ​​the electrode material is 2.0 m 2 / g-10.0m 2 / g. Optionally, the specific surface area of ​​the electrode material can be 2.0m 2 / g, 4.0m 2 / g, 6.0m 2 / g, 8.0m 2 / g, 10.0m 2 / g, etc., or the range between any one or any two thereof, is not limited here. In this embodiment, if the specific surface area is too small, it indicates that the coating layer is too thick, which increases the steric hindrance of sodium ions entering the closed pores from the electrolyte, and the battery polarization becomes larger; if the specific surface area is too large, it indicates that the effect of converting the open pores into closed pores is not ideal, the activity of the pore sodium storage site is low, and the effect of metal nitride modification of the closed pores is not ideal.

[0078] The present application also provides a method for preparing an electrode material, such as Figure 1 As shown, the following steps are included:

[0079] S1, pre-carbonizing the carbon source to obtain a pre-carbonized material;

[0080] S2, performing pore forming treatment on the pre-carbonized material, crushing it, and obtaining a first precursor;

[0081] S3, immersing the first precursor in a metal salt solution to obtain an intermediate;

[0082] S4, reacting the intermediate with a process gas at a high temperature to obtain a second precursor;

[0083] S5. Sintering the second precursor at high temperature to obtain an electrode material.

[0084] In the above scheme, the present application prepares a first precursor with abundant open pores by pre-carbonization treatment and pore-forming treatment, and then loads the metal salt on the surface and pores of the first precursor by solution impregnation, and then converts the metal salt into nano metal oxide at high temperature, and the process gas converts the nano metal oxide into a stable metal nitride, and finally, by high temperature sintering, the open pores of the second precursor are converted into closed pores, and the metal nitride is restricted from escaping from the pores, thereby obtaining a metal nitride-modified electrode material. In this embodiment, through the processes of metal salt solution impregnation, secondary conversion (metal salt is first converted into metal oxide, and then into metal nitride), high temperature sintering, etc., the metal nitride is nano-sized and uniformly loaded on the surface of the electrode material and the closed pores, and the electronic conductivity of the closed pore area is improved, which provides a prerequisite for improving the pore sodium storage activity of the electrode material; in addition, the conversion of the open pores into closed pores provides a structural basis for improving the pore sodium storage capacity of the negative electrode material, and is conducive to fixing the metal nitride in the closed pores.

[0085] The preparation method of the present application is described in detail below with reference to the examples:

[0086] S1. Pre-carbonizing the carbon source to obtain a pre-carbonized material.

[0087] In some embodiments, the carbon source includes any one or more combinations of plant carbon sources, sugar carbon sources, resin carbon sources, and polymer carbon sources. Preferably, the plant carbon source includes any one or more combinations of coconut shells, almond shells, pistachio shells, macadamia shells, jujube shells, chestnut shells, hazelnut shells, peanut shells, walnut shells, peach shells, cotton, wood, bamboo, bagasse, straw, and lignin; preferably, the sugar carbon source includes any one or more combinations of sucrose, maltose, lactose, fructose, starch, and cellulose; preferably, the resin carbon source includes any one or more combinations of phenolic resins, polyimide resins, polyester resins, polyaldehyde resins, polyolefin resins, and polyacrylic acid resins; preferably, the polymer carbon source includes any one or more combinations of polyfurfuryl alcohol, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, natural rubber, and polyacrylonitrile.

[0088] In some embodiments, the temperature of the pre-carbonization treatment is 450° C.-650° C. Optionally, the temperature of the pre-carbonization treatment can be any one of 450° C., 500° C., 550° C., 600° C., 650° C., etc., or a range between any two thereof, which is not limited here.

[0089] In some embodiments, the pre-carbonization treatment time is 0.5h-24h. Optionally, the pre-carbonization treatment time can be any one of 0.5h, 1h, 4h, 8h, 12h, 16h, 20h, 24h, etc. or a range between any two thereof, which is not limited here.

[0090] In some embodiments, the pre-carbonization treatment is performed in an inert gas atmosphere or an oxygen-deficient atmosphere. The inert gas atmosphere includes any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, or krypton atmosphere, or a combination of at least two thereof, and the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of ≤1 wt%.

[0091] S2. Performing pore-forming treatment on the pre-carbonized material and crushing it to obtain a first precursor.

[0092] In some embodiments, the pulverization process includes: pulverizing the product of the pore-forming process to a median particle size of 3 μm-15 μm. Optionally, the pulverization process includes a combination of one or more of ball milling, air flow milling, mechanical milling, and roller pressing milling.

[0093] In some embodiments, the pore-forming treatment includes solid-phase pore-forming, and the solid-phase pore-forming includes the following steps: under inert atmosphere conditions, the pre-carbonized material is uniformly mixed with a solid-phase pore-forming agent, and subjected to high-temperature treatment to obtain a solid-phase pore-forming modified material.

[0094] In some embodiments, in the solid phase pore formation step, the temperature of the high temperature treatment is 600°C-800°C, and the time of the high temperature treatment is 0.5h-8h. Optionally, the temperature of the high temperature treatment can be any one of 600°C, 650°C, 700°C, 740°C, 780°C, 800°C, etc., or a range between any two thereof, which is not limited here; the time of the high temperature treatment can be any one of 0.5h, 1h, 2h, 4h, 6h, 8h, etc., or a range between any two thereof, which is not limited here.

[0095] In some embodiments, the mass ratio of the pre-carbonized material to the solid-phase pore former is 1:(0.4-3.0). Optionally, the mass ratio of the pre-carbonized material to the solid-phase pore former can be any one of 1:0.4, 1:0.8, 1:1, 1:1.5, 1:2.0, 1:2.5, 1:3.0, etc., or a range between any two of them, which is not limited here. In this embodiment, if the amount of solid-phase pore former added is too small, it is easy to cause the pore volume of the first precursor to be too small, and the effect of the electrode material loading metal nitride is not ideal; if the amount of solid-phase pore former added is too much, it is easy to cause the pore size generated in the pore-forming process to be too large, the specific surface area of ​​the first precursor is too high, and the excessive pore size is not conducive to the first precursor adsorbing metal salts, resulting in a reduction in the amount of metal nitride loaded on the electrode material.

[0096] In some embodiments, the solid phase pore former includes at least one of sodium hydroxide, potassium hydroxide, sodium oxide, potassium oxide, sodium carbonate, potassium carbonate, potassium bicarbonate, sodium bicarbonate, calcium oxide, and zinc chloride.

[0097] In some embodiments, in the solid phase pore formation step, the inert atmosphere includes any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two thereof.

[0098] In some embodiments, the solid-phase pore-forming treatment further includes a solid-phase pore-forming modification material purification treatment, and the solid-phase pore-forming modification material purification treatment includes: uniformly mixing the solid-phase pore-forming modification material, acid solution, and pure water, and stirring for 0.5h-24h, performing solid-liquid separation after stirring, washing the purified product obtained by solid-liquid separation to a pH of 2.5-4.5, and drying. In this embodiment, if the solid-phase pore-forming modification material purification treatment is not performed, it is easy to cause the residual pore-forming agent or impurities to occupy the pore volume of the first precursor. When the first precursor is subsequently immersed in a metal salt solution, the amount of metal salt adsorbed by the first precursor is reduced, resulting in less loaded metal nitride content in the electrode material, a reduction in the pore volume with sodium storage activity, and a decrease in the conductivity of the electrode material, which in turn leads to a decrease in the specific capacity, rate performance, and cycle performance of the electrode material; in addition, the residual pore-forming agent and impurities in the first precursor are easy to react with the electrolyte during the battery charging and discharging process, catalyzing the battery to self-discharge, resulting in a decrease in the battery's initial efficiency and life.

[0099] In some embodiments, the mass ratio of the solid-phase pore-forming modification material, the acid solution, and the pure water is 1:(0.5-2):(2-5). Optionally, the mass ratio of the solid-phase pore-forming modification material, the acid solution, and the pure water can be any one of 1:0.5:2, 1:1:3, 1:2:4, 1:2:5, 1:0.5:5, etc., or a range between any two of them, which is not limited here.

[0100] In some embodiments, the acid solution may be one of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid, or a combination of at least two thereof.

[0101] In some embodiments, the pore-forming treatment includes gas-phase pore-forming, and the gas-phase pore-forming includes the following steps: placing the pre-carbonized material in a reaction furnace, introducing a pore-forming gas, heating it to a first temperature and then keeping it warm to obtain a gas-phase pore-forming modified material.

[0102] In some embodiments, in the gas phase pore forming step, the first temperature is 800°C-1000°C, and the holding time is 1h-8h. Optionally, the first temperature can be any one of 800°C, 850°C, 900°C, 950°C, 1000°C, etc., or a range between any two thereof, which is not limited here; the holding time can be any one of 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc., or a range between any two thereof, which is not limited here.

[0103] In some embodiments, the pore-forming gas includes any one of water vapor, carbon dioxide, chlorine, oxygen, ozone, and air, or a combination of at least two thereof.

[0104] In some embodiments, the gas phase pore forming treatment further includes a gas phase pore forming modification material purification treatment, specifically comprising: mixing the gas phase pore forming modification material, acid solution, and pure water in a mass ratio of 1: (0.5-2): (1.2-5) and stirring for 0.5h-24h, performing solid-liquid separation after stirring, washing the purified product obtained by solid-liquid separation to a pH of 4-8, and drying. Optionally, the mass ratio between the gas phase pore forming modification material, acid solution, and pure water can be any one of 1:0.5:1.2, 1:1:3, 1:2:1.2, 1:2:5, 1:0.5:5, etc., or a range between any two of them, which is not limited here.

[0105] S3, immersing the first precursor in a metal salt solution to obtain an intermediate.

[0106] In some embodiments, step S3 specifically includes: immersing the first precursor in a metal salt solution, stirring for 3h-24h, separating the solid from the liquid, and drying to obtain an intermediate.

[0107] In some embodiments, the concentration of the metal salt solution is 0.5wt%-5wt%, and the mass ratio of the first precursor to the metal salt solution is 1:(3-20). Optionally, the concentration of the metal salt solution can be any one of 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, etc., or a range between any two of them, which is not limited here; the mass ratio of the first precursor to the metal salt solution can be any one of 1:3, 1:5, 1:10, 1:12, 1:15, 1:18, 1:20, etc., or a range between any two of them, which is not limited here.

[0108] In this embodiment, when the content of the metal salt solution is too little, it is easy to cause the content of the metal nitride finally doped on the electrode material to be too low, thereby causing the specific capacity, rate performance and cycle performance of the electrode material to decrease; if the content of the metal salt solution is too much, it is easy to cause the content of the metal nitride on the final electrode material to be too high, and the pore volume of the obtained electrode material that can be used for sodium storage will decrease, and the pore sodium storage sites will decrease, resulting in a decrease in capacity performance.

[0109] In some embodiments, the median particle size of the first precursor is 3 μm-15 μm. Optionally, the median particle size of the first precursor can be any one of 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, etc., or a range between any two thereof, which is not limited here.

[0110] In some embodiments, the metal salt includes a soluble salt of Co, Ni, Cu, V, Ti, Mn, Fe or Zr, and the soluble salt includes one or a combination of at least two of sulfates, nitrates, chlorides, etc.

[0111] S4. reacting the intermediate with a process gas at a high temperature to obtain a second precursor.

[0112] In step S4, during the reaction of the intermediate with the process gas at high temperature, the metal salt on the intermediate is converted into nano metal oxide at high temperature, and the process gas then converts the nano metal oxide into stable metal nitride.

[0113] In some embodiments, step S4 specifically includes: placing the intermediate in a reaction furnace under an inert atmosphere, introducing a process gas, heating the intermediate to a second temperature, then maintaining the temperature, and cooling the intermediate to obtain a second precursor.

[0114] In some embodiments, the second temperature is 1000°C-1400°C, and the holding time is 3h-10h. In this embodiment, if the second temperature is too low, it is easy to cause the metal oxide to fail to be converted or only partially converted into metal nitride; if the second temperature is too high, it is easy to cause the generated metal nitride to partially or completely sublimate, and the effect of metal nitride on closed pore modification is not ideal. Optionally, the second temperature can be any one of 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, etc., or a range between any two, which is not limited here; the holding time can be any one of 3h, 4h, 6h, 7h, 8h, 9h, 10h, etc., or a range between any two, which is not limited here.

[0115] In some embodiments, the inert atmosphere includes any one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere, or a krypton atmosphere, or a combination of at least two thereof.

[0116] In some embodiments, the process gas is one or a combination of at least two of ammonia, methylamine, ethylamine, diethylamine, n-propylamine, and isopropylamine. In this embodiment, the process gas contains ammonia or generates ammonia after cracking, and ammonia and metal oxide can react at high temperature to generate metal nitride.

[0117] Preferably, the process gas includes at least one of methylamine, ethylamine, diethylamine, n-propylamine, and isopropylamine. In the present embodiment, methylamine, ethylamine, diethylamine, n-propylamine, and isopropylamine are all process gases containing carbon atoms and amino groups. In step S4, the process gas can produce ammonia, which can react with metal oxides at high temperatures to generate metal nitrides. At the same time, the process gas contains carbon atoms and can be used as a coating carbon source to carbon-coat the intermediate, reduce the pore size of the intermediate opening, and facilitate the conversion of the intermediate opening into closed pores, inhibiting the generated metal nitride from escaping from the pore structure, thereby ensuring the effectiveness of the metal nitride in modifying the closed pores.

[0118] S5. Sintering the second precursor at high temperature to obtain an electrode material.

[0119] In some embodiments, in step S5, high temperature sintering is carried out under inert atmosphere conditions, the temperature of high temperature sintering is 1200℃-1500℃, and the time of high temperature sintering is 0.5h-10h. In this embodiment, if the temperature of high temperature sintering is too low, it is easy to cause the open pores to be unable to be effectively converted into closed pores, and the open pores do not have sodium storage activity, thereby reducing the sodium storage utilization rate of the pore volume of the electrode material; if the temperature of high temperature sintering is too high, it is easy to cause the sublimation of metal nitrides and the collapse of all or part of the closed pores, the decrease in the porosity of the electrode material particles and the reduction in the spacing between carbon layers, thereby causing the metal nitride to improve the electric field in the central area of ​​the closed pores and the storage activity. The effect is not ideal. Optionally, the temperature of high temperature sintering can be any one of 1200℃, 1300℃, 1400℃, 1500℃, etc., or a range between any two, which is not limited here; the time of high temperature sintering can be any one of 0.5h, 1h, 3h, 5h, 7h, 9h, 10h, etc., or a range between any two, which is not limited here.

[0120] In some embodiments, before the second precursor is subjected to high temperature sintering, the following step is further included: mixing the coated carbon source and the second precursor uniformly. In this embodiment, the coated carbon source and the second precursor are uniformly mixed, and during high temperature sintering, the coated carbon source can convert the open pores into closed pores, restrict the escape of metal nitrides from the pores, effectively fix the metal nitrides in the pore structure, and increase the pore sodium storage sites, thereby improving the sodium storage capacity, rate performance, and cycle performance of the electrode material.

[0121] In some embodiments, the mass ratio of the second precursor to the coated carbon source is 1:(0.01-0.1). Optionally, the mass ratio of the second precursor to the coated carbon source can be any one of 1:0.01, 1:0.02, 1:0.04, 1:0.06, 1:0.08, 1:0.1, etc., or a range between any two of them, which is not limited here.

[0122] In some embodiments, the coated carbon source includes any one or more combinations of asphalt, sucrose, phenolic resin, polyacrylic resin, glucose, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyvinyl alcohol, epoxy resin, urea-formaldehyde resin, and melamine resin.

[0123] In some embodiments, the inert atmosphere is any one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere, or a krypton atmosphere, or a combination of at least two thereof.

[0124] The present application also provides a sodium ion battery, comprising the electrode material as described above or the electrode material prepared by the preparation method as described above.

[0125] The present application is further described below through specific embodiments.

[0126] Example 1

[0127] (1) In a tubular furnace, coconut shells were heated to 500°C under nitrogen, kept at this temperature for 12 h, cooled, and crushed using a crusher with a mesh size of 5 mm to obtain pre-carbonized materials.

[0128] (2) The pre-carbonized material and sodium hydroxide were mixed in a mass ratio of 1:1.5 and placed in a box furnace, heated to 700°C under a nitrogen atmosphere, kept warm for 1 hour, cooled, washed with pure water until the pH value was 9, and solid-liquid separation was performed to obtain a solid-phase pore-forming modified material; then the solid-phase pore-forming modified material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and water were mixed in a mass ratio of 1:1:0.1:5, heated to 80°C, stirred for 12 hours, solid-liquid separation was performed, washed to a pH value of 3.5, dried, and ball-milled to a median particle size of 7μm to obtain a first precursor;

[0129] (3) Prepare a cobalt nitrate solution with a concentration of 2.5wt%. Immerse 1 times the mass of the first precursor in 10 times the mass of the cobalt nitrate solution, stir for 12 hours, separate the solid and liquid, and dry to obtain an intermediate. Place the intermediate in a furnace, heat it to 1200°C under a nitrogen atmosphere, introduce ammonia, keep it warm for 5 hours, and cool it to obtain a second precursor.

[0130] (4) The second precursor and asphalt were mixed in a mass ratio of 1:0.02, and the mixture was transferred to a tube furnace, heated to 1300° C. under a nitrogen atmosphere and sintered for 3 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material.

[0131] Example 2

[0132] (1) The phenolic resin was heated to 650° C. in a box furnace under a helium atmosphere, kept at this temperature for 0.5 h, cooled, and the obtained material was crushed with a crusher having a mesh size of 3 mm to obtain a pre-carbonized material.

[0133] (2) The pre-carbonized material and sodium carbonate are mixed in a mass ratio of 1:3, placed in a box furnace, heated to 800°C under a nitrogen atmosphere, kept warm for 0.5 hours, cooled, washed with pure water until the pH value is 9, and solid-liquid separation is performed to obtain a solid-phase pore-forming modified material; then the solid-phase pore-forming modified material, hydrochloric acid (concentration of 31wt%) and water are mixed in a mass ratio of 1:0.5:3, heated to 60°C, stirred for 1 hour, solid-liquid separation is performed, washed to a pH value of 3.5, dried, and air flow crushed to a median particle size of 3μm to obtain a first precursor;

[0134] (3) Prepare a 0.5wt% ferric sulfate solution, immerse 1 times the mass of the first precursor in 3 times the mass of the ferric sulfate solution, stir for 3 hours, separate the solid and liquid, and dry to obtain an intermediate. Place the obtained intermediate in a furnace, heat it to 1400°C under a neon atmosphere, introduce methylamine, keep it warm for 10 hours, and cool it to obtain a second precursor;

[0135] (4) The second precursor was transferred to a tube furnace, heated to 1500° C. in a helium atmosphere, sintered for 4 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material.

[0136] Example 3

[0137] (1) The sucrose was heated to 450° C. in an argon atmosphere in a box furnace, kept at this temperature for 24 h, cooled, and the obtained material was crushed with a crusher having a mesh size of 1 mm to obtain a pre-carbonized material.

[0138] (2) Mix the pre-carbonized material and zinc chloride in a mass ratio of 1:0.5, place in a box furnace, heat to 700°C under a nitrogen atmosphere, keep warm for 2 hours, and cool. Add pure water to wash until the pH is 9, separate the solid and liquid, and obtain a solid-phase pore-forming modified material; then mix the solid-phase pore-forming modified material, hydrochloric acid (concentration of 31wt%) and water in a mass ratio of 1:1:5, stir for 1 hour, separate the solid and liquid, wash to a pH of 3.5, and dry. Grind the obtained material into a gas stream to a median particle size of 5μm to obtain a first precursor;

[0139] (3) Prepare a nickel chloride solution with a concentration of 1wt%. Immerse 1 times the mass of the first precursor in a nickel chloride solution with a mass of 20 times, stir for 4 hours, separate the solid and liquid, and dry to obtain an intermediate. Place the intermediate in a furnace, heat it to 1100°C under argon, introduce ethylamine, keep it warm for 3 hours, and cool it to obtain a second precursor;

[0140] (4) The second precursor was transferred to a tube furnace, heated to 1200° C. in a krypton atmosphere, sintered for 10 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material.

[0141] Example 4

[0142] (1) Polyaniline was heated to 500° C. in a tubular furnace under a krypton atmosphere, kept at this temperature for 2 h, cooled, and the obtained material was crushed with a crusher having a mesh size of 3 mm to obtain a pre-carbonized material.

[0143] (2) placing the pre-carbonized material in a box furnace, heating it to 1000° C. under a nitrogen atmosphere, introducing water vapor, keeping the temperature for 3 hours, cooling, and pulverizing the obtained material gas flow to a median particle size of about 15 μm to obtain a first precursor;

[0144] (3) preparing a copper nitrate solution with a concentration of 1.5 wt%, immersing 1 times the mass of the first precursor in 8 times the mass of the copper sulfur nitrate solution, stirring for 4 hours, separating the solid and the liquid, drying to obtain an intermediate, placing the intermediate in a furnace, heating it to 1200° C. under argon, introducing n-propylamine, keeping the temperature for 6 hours, and cooling to obtain a second precursor;

[0145] (4) The second precursor was transferred to a tube furnace, heated to 1300° C. in a neon atmosphere, sintered for 0.5 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material.

[0146] Example 5

[0147] (1) The walnut shells were heated to 550°C in a box furnace under a nitrogen atmosphere, kept at this temperature for 8 h, cooled, and the obtained material was crushed with a crusher with a mesh size of 3 mm to obtain a pre-carbonized material.

[0148] (2) The pre-carbonized material and potassium hydroxide were mixed in a mass ratio of 1:0.4, placed in a box furnace, heated to 600°C under nitrogen, kept warm for 8 hours, cooled, washed with pure water until the pH value was 9, and solid-liquid separation was performed to obtain a solid-phase pore-forming modified material; then the solid-phase pore-forming modified material, hydrochloric acid (concentration of 31wt%) and water were mixed in a mass ratio of 1:2:3, heated to 70°C, stirred for 4 hours, solid-liquid separation was performed, washed to a pH value of 3.5, dried, and mechanically crushed to a median particle size of 10μm to obtain a first precursor;

[0149] (3) Prepare a titanium chloride solution with a concentration of 5wt%, immerse 1 times the mass of the first precursor in the titanium chloride solution with a concentration of 10 times the mass, stir for 2 hours, separate the solid and liquid, and dry to obtain an intermediate. Place the intermediate in a furnace, heat it to 1000°C under nitrogen, introduce diethylamine, keep it warm for 10 hours, and cool it to obtain a second precursor.

[0150] (4) The second precursor and glucose were mixed in a mass ratio of 1:0.1, transferred to a tube furnace, heated to 1400° C. in a helium atmosphere, sintered for 8 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material.

[0151] Example 6

[0152] (1) The starch was heated to 600° C. in an oxygen-deficient atmosphere in a box furnace, kept at this temperature for 4 h, cooled, and the obtained material was crushed with a crusher having a mesh size of 5 mm to obtain a pre-carbonized material.

[0153] (2) The pre-carbonized material and sodium hydroxide were mixed in a mass ratio of 1:1.2, placed in a box furnace, heated to 700°C under argon, kept warm for 1 hour, cooled, washed with pure water until the pH value was 9, and solid-liquid separation was performed to obtain a solid-phase pore-forming modified material; then the solid-phase pore-forming modified material, sulfuric acid (concentration of 92.5wt%) and water were mixed in a mass ratio of 1:0.8:3, stirred for 6 hours, solid-liquid separation was performed, washed to a pH value of 3.5, dried, and air flow crushed to a median particle size of 3 μm to obtain a first precursor;

[0154] (3) Prepare a 2wt% manganese nitrate solution, immerse 1 times the mass of the first precursor in 10 times the mass of the manganese nitrate solution, stir for 3 hours, separate the solid and liquid, and dry to obtain an intermediate. Place the intermediate in a furnace, heat it to 1100°C under a nitrogen atmosphere, introduce ammonia, keep it warm for 10 hours, and cool it to obtain a second precursor;

[0155] (4) The second precursor was transferred to a box furnace, heated to 1300° C. in a nitrogen atmosphere, sintered for 3 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material.

[0156] Example 7

[0157] The difference between Example 7 and Example 6 is:

[0158] Step (4) is: mixing the second precursor and asphalt in a mass ratio of 1:0.02, transferring the mixture to a box furnace, heating to 1300°C under a nitrogen atmosphere and sintering for 3 hours, cooling, and sieving with a 325-mesh sieve to obtain an electrode material; the rest is the same as Example 6.

[0159] Example 8

[0160] The difference between Example 8 and Example 6 is:

[0161] Step (3) is: prepare a manganese nitrate solution with a concentration of 2wt%, immerse 1 times the mass of the first precursor in 10 times the mass of the manganese nitrate solution, stir for 3 hours, separate the solid and liquid, and dry to obtain an intermediate. Place the intermediate in a furnace, heat it to 1100°C under a nitrogen atmosphere, introduce methylamine, keep it warm for 10 hours, and cool it to obtain a second precursor; the rest is the same as Example 6.

[0162] Example 9

[0163] The difference between Example 9 and Example 2 is:

[0164] Step (1) is: phenolic resin and starch are mixed in a mass ratio of 1:1 to obtain a mixed carbon source, the mixed carbon source is heated to 650° C. in a box furnace under a helium atmosphere, kept warm for 0.5 h, cooled, and the obtained material is crushed with a crusher with a mesh size of 3 mm to obtain a pre-carbonized material; the rest is the same as Example 2.

[0165] Example 10

[0166] The difference between Example 10 and Example 2 is:

[0167] Step (3) is: prepare a 5wt% ferric sulfate solution, immerse 1 times the mass of the first precursor in 20 times the mass of the ferric sulfate solution, stir for 3 hours, separate the solid and liquid, and dry to obtain an intermediate. The obtained intermediate is placed in a furnace, heated to 1400°C under a neon atmosphere, methylamine is introduced, kept warm for 10 hours, and cooled to obtain a second precursor; the rest is the same as in Example 2.

[0168] Embodiment 11

[0169] The difference between Example 11 and Example 1 is:

[0170] Step (2) is: the pre-carbonized material and sodium hydroxide are mixed in a mass ratio of 1:0.2 and placed in a box furnace, the temperature is raised to 700°C under a nitrogen atmosphere, kept warm for 1 hour, cooled, pure water is added to wash until the pH is 9, solid-liquid separation is performed, and a solid-phase pore-forming modified material is obtained; then the solid-phase pore-forming modified material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and water are mixed in a mass ratio of 1:1:0.1:5, heated to 80°C, stirred for 12 hours, solid-liquid separation is performed, washed to a pH of 3.5, dried, and ball-milled to a median particle size of 7μm to obtain a first precursor; the rest is the same as Example 1.

[0171] Example 12

[0172] The difference between Example 12 and Example 1 is:

[0173] Step (2) is: the pre-carbonized material and sodium hydroxide are mixed in a mass ratio of 1:4 and placed in a box furnace, the temperature is raised to 700°C under a nitrogen atmosphere, kept warm for 1h, cooled, pure water is added to wash until the pH is 9, solid-liquid separation is performed, and a solid-phase pore-forming modified material is obtained; then the solid-phase pore-forming modified material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and water are mixed in a mass ratio of 1:1:0.1:5, heated to 80°C, stirred for 12h, solid-liquid separation is performed, washed to a pH of 3.5, dried, and ball-milled to a median particle size of 7μm to obtain a first precursor; the rest is the same as Example 1.

[0174] Embodiment 13

[0175] The difference between Example 13 and Example 1 is:

[0176] Step (2) is: mixing the pre-carbonized material and sodium hydroxide in a mass ratio of 1:1.5 and placing them in a box furnace, heating them to 700°C under nitrogen, keeping them warm for 1H, cooling them, adding pure water to wash them until the pH is 9, separating the solid and liquid, drying them, and ball milling them to a median particle size of 7μm to obtain a first precursor; the rest is the same as Example 1.

[0177] Embodiment 14

[0178] The difference between Example 14 and Example 1 is:

[0179] Step (3) is: prepare a cobalt nitrate solution with a concentration of 2.5wt%. Immerse 1 times the mass of the first precursor in 10 times the mass of the cobalt nitrate solution, stir for 12 hours, separate the solid and liquid, dry to obtain an intermediate, place the intermediate in a furnace, heat to 700°C under a nitrogen atmosphere, introduce ammonia, keep warm for 5 hours, cool to obtain a second precursor; the rest is the same as Example 1.

[0180] Embodiment 15

[0181] The difference between Example 15 and Example 1 is:

[0182] Step (3) is: prepare a cobalt nitrate solution with a concentration of 2.5wt%. Immerse 1 times the mass of the first precursor in 10 times the mass of the cobalt nitrate solution, stir for 12 hours, separate the solid and liquid, dry to obtain an intermediate, place the intermediate in a furnace, heat to 1500°C under a nitrogen atmosphere, introduce ammonia, keep warm for 5 hours, cool to obtain a second precursor; the rest is the same as Example 1.

[0183] Example 16

[0184] The difference between Example 16 and Example 1 is:

[0185] Step (4) is: the second precursor and asphalt are mixed in a mass ratio of 1:0.02, the mixture is transferred to a tubular furnace, heated to 1100° C. under a nitrogen atmosphere and sintered for 3 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material; the rest is the same as in Example 1.

[0186] Embodiment 17

[0187] The difference between Example 17 and Example 1 is:

[0188] Step (4) is: the second precursor and asphalt are mixed in a mass ratio of 1:0.02, the mixture is transferred to a tubular furnace, heated to 1600° C. under a nitrogen atmosphere and sintered for 3 h, cooled, and sieved with a 325-mesh sieve to obtain an electrode material; the rest is the same as in Example 1.

[0189] Embodiment 18

[0190] The difference between Example 18 and Example 2 is:

[0191] Step (3) is: prepare a 0.5wt% ferric sulfate solution, immerse 1 times the mass of the first precursor in 2 times the mass of the ferric sulfate solution, stir for 3 hours, separate the solid and liquid, and dry to obtain an intermediate. The obtained intermediate is placed in a furnace, heated to 1400°C under a neon atmosphere, methylamine is introduced, kept warm for 10 hours, and cooled to obtain a second precursor; the rest is the same as in Example 1.

[0192] Embodiment 19

[0193] The difference between Example 19 and Example 2 is:

[0194] Step (3) is: prepare a 5wt% ferric sulfate solution, immerse 1 times the mass of the first precursor in 25 times the mass of the ferric sulfate solution, stir for 3 hours, separate the solid and liquid, and dry to obtain an intermediate. The obtained intermediate is placed in a furnace, heated to 1400°C under a neon atmosphere, methylamine is introduced, kept warm for 10 hours, and cooled to obtain a second precursor; the rest is the same as in Example 1.

[0195] Comparative Example 1

[0196] The difference between Comparative Example 1 and Example 1 is:

[0197] Step (2) is: mixing the pre-carbonized material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and water in a mass ratio of 1:1:0.1:5, heating to 80°C, stirring for 12h, solid-liquid separation, washing to a pH value of 3.5, drying, and ball milling to a median particle size of 7μm to obtain a first precursor; the rest is the same as Example 1.

[0198] Comparative Example 2

[0199] The difference between Comparative Example 2 and Example 1 is:

[0200] Step (3) is: placing the first precursor in a furnace, heating it to 1200° C. under nitrogen, introducing ammonia, keeping the temperature for 5 hours, cooling, and obtaining the second precursor; the rest is the same as in Example 1.

[0201] Comparative Example 3

[0202] The difference between Comparative Example 3 and Example 1 is:

[0203] Step (3) is: prepare a cobalt nitrate solution with a concentration of 2.5wt%. Immerse 1 times the mass of the first precursor in 10 times the mass of the cobalt nitrate solution, stir for 12 hours, separate the solid and liquid, dry to obtain an intermediate, place the intermediate in a furnace, heat to 1200°C under nitrogen, keep warm for 5 hours, cool to obtain a second precursor; the rest is the same as in Example 1.

[0204] Comparative Example 4

[0205] (1) In a tubular furnace, the coconut shell was heated to 500° C. under nitrogen, kept at this temperature for 12 h, cooled, and the obtained material was crushed with a crusher having a mesh size of 5 mm to obtain a pre-carbonized material;

[0206] (2) mixing the pre-carbonized material, hydrochloric acid (concentration of 31 wt%), hydrofluoric acid (concentration of 55 wt%) and water in a mass ratio of 1:1:0.1:5, heating to 80°C, stirring for 12 h, solid-liquid separation, washing to a pH value of 3.5, drying, and ball milling to a median particle size of 7 μm to obtain a first precursor;

[0207] (3) The first precursor and asphalt were mixed in a mass ratio of 1:0.02, and the mixture was transferred to a tube furnace. The mixture was heated to 1300° C. and sintered for 3 h under a nitrogen atmosphere. The mixture was cooled and sieved with a 325-mesh sieve to obtain an electrode material.

[0208] Test Method

[0209] The following tests were performed on the electrode materials prepared in Examples 1 to 19 and Comparative Examples 1 to 4:

[0210] (I) 3T powder compaction density (g / cm 3 ) and particle porosity test:

[0211] The test method is: Shenzhen Sansi Zongheng Battery Powder Compacted Density Tester UTM7305 is used for testing. The sample of specified mass is placed in the mold and a pressure of 3.0T is applied. The pressure is maintained for 30S and then released to 20N to test its thickness. According to the formula ρ=10*(m / S*H), the compacted density (unit: g / cm2) is automatically output on the instrument software. 3 ).

[0212] Particle porosity = (1-ρ / ρ0)*100%;

[0213] Where ρ is the 3T powder compaction density of the electrode material (g / cm3); ρ0 is the 3T powder compaction density of the reference product (the reference product is a coconut shell-based hard carbon sintered at 1250°C with a median particle size of 6 μm without pore modification), and ρ0 is agreed to be 1.05 g / cm 3The physical meaning of particle porosity is the ratio of the pore volume of pores generated by pore-forming modification or the inherent pores of carbon derived from carbon source to the electrode material (carbon base volume + pore volume). The particle porosity of the modified reference product is specified to be 0.

[0214] (II) Powder conductivity test:

[0215] The test method is: the powder conductivity of the material is tested using Mitsubishi Chemical's MCP-PD51 tester. The sample is added and tested at 20KN to obtain the conductivity data (unit S / cm).

[0216] (III) Test of median particle size:

[0217] The test method is: using MASTERSIZER3000 for testing. The particle refractive index is 2.42, the absorption rate is 1.0, the dispersant is water, and the dispersant refractive index is 1.33. The method is: weigh about 0.1g of sample in a 100mL beaker, add water to 50mL, ultrasonic for 1min, add sample to the shading degree of 8-12%, and start internal ultrasonic testing.

[0218] (IV) Carbon layer spacing content test:

[0219] The test method is: using a Panalytical X'Pert PRO MPD tester, using Cu target Kα rays (wavelength λ = 0.1541nm) as the light source, and testing to obtain XRD data in the 2Theta range of 10°-90°. The carbon layer spacing is calculated by substituting the diffraction angle (002) of XRD into the Scherrer formula (unit: nm).

[0220] (V) Specific surface area test:

[0221] The test method is: using a Macbeth tester (model ASAP2460) to perform nitrogen adsorption test at 77K to obtain the specific surface area, which is calculated using the BET formula (unit: m 2 / g).

[0222] (VI) SEM photo hard carbon test:

[0223] The testing method is: scanning the sample with a Hitachi S4800 scanning electron microscope to obtain a SEM photo.

[0224] (VII) Metal nitride content test:

[0225] Sample pretreatment method:

[0226] (A) placing the electrode material (HC-1) obtained in the present invention in a vacuum furnace, heating it to 2200° C. under vacuum atmosphere, keeping the temperature for 4 hours, and cooling it to room temperature to obtain electrode material HC-2;

[0227] (B) Prepare 1.0M hydrochloric acid solution, immerse 1 times the mass of electrode material into 10 times the 1.0M hydrochloric acid solution, stir for 6 hours, separate the solid and liquid, use pure water to wash until the pH is ≥4, and dry to obtain hard carbon HC-3. Place the dried HC-3 in a vacuum furnace, heat it to 2200°C under vacuum atmosphere, keep it warm for 4 hours, cool it to room temperature, take it out, and obtain electrode material HC-4;

[0228] Ash content test method: Dry the electrode material at 100℃ for 4 hours; pre-burn the ash crucible at 900℃ for 0.5 hours, place it in a dryer to cool to room temperature, weigh it, get the mass of the empty crucible, weigh the dried electrode material (about 2g), place it in a muffle furnace and burn it at 900℃ to constant weight (about 2 hours), place it in a dryer to cool to room temperature, weigh it, and the ash content value is according to the formula:

[0229] Ash content (wt%) = (mass of the completely burned crucible - mass of the empty crucible) * 100% / mass of the sample.

[0230] The principle of the metal nitride content test of the present invention is:

[0231] (A) Taking advantage of the sublimation characteristics of metal nitrides in a vacuum atmosphere and at high temperature (2200°C), the total metal nitride content of the obtained electrode material was tested;

[0232] (B) The metal nitrides and other impurities on the surface of the negative electrode are converted into soluble substances after purification by hydrochloric acid solution and removed by washing with pure water. The hydrogen ions of 1.0M hydrochloric acid solution are difficult to enter the closed pores, so the metal nitrides in the closed pores are retained in the electrode material after hydrochloric acid purification. The electrode material purified by hydrochloric acid is treated in a vacuum atmosphere and high temperature (2200℃), which can convert the metal nitrides in the closed pores into gas molecules, thereby removing the metal nitrides in the closed pores, and then measuring the samples after high temperature treatment.

[0233] The ash contents of HC-1, HC-2, HC-3 and HC-4 were tested as A1, A2, A3 and A4 respectively.

[0234] Total content of metal nitride (wt%) = A1-A2*(100-A1) / (100-A2);

[0235] The content of metal nitride in the closed pores (wt%) = A3-A4*(100-A3) / (100-A4).

[0236] (VIII) Test of specific capacity and initial efficiency:

[0237] The electrode material, conductive agent and binder obtained in the embodiment and comparative example were mixed in a mass percentage of 91:3:6, and the mixture was adjusted to a solid content of 50% with deionized water. The mixture was coated on a copper foil current collector on one side, dried at 130°C for 2 hours, and rolled to a surface density of 5.5±0.5 mg / cm 2 , cut into 14mm diameter discs to make pole pieces; use glass fiber GD-120 as diaphragm, 16mm diameter sodium sheet as counter electrode, disperse 1M sodium hexafluorophosphate in diethylene glycol dimethyl ether = 100Vol% organic solvent to make electrolyte, assemble electrolyte, pole piece, diaphragm, counter electrode and CR2032 battery shell into button cell; at room temperature (about 25℃), test the button cell on Arbin battery test system, set the nominal specific capacity to 300mAh / g, first discharge at 0.1C constant current to 1mV, then discharge at 1mV constant voltage to current density of 3.5*10 -6 A, discharge cut-off; after standing, then charge at 0.1C, cut-off voltage 2V, test results are shown in Table 2. Specific capacity (mAh / g) is the first charge capacity divided by the weight of the electrode material contained in the negative electrode sheet, and the first efficiency is the ratio of the first charge capacity to the first discharge capacity.

[0238] (IX) Electrochemical performance test of soft-pack finished battery:

[0239] BNH-O3A, a layered oxide of BYD, was used as the positive electrode. The positive electrode material, conductive agent and adhesive were mixed in a mass percentage of 96:2:2. The mixture was adjusted to a solid content of 50% with N-methylpyrrolidone, and then coated on both sides of the aluminum foil current collector, dried, and rolled to control the surface density to 300 g / m 2 The electrode materials, conductive agent and binder obtained in Examples 1 to 10 and Comparative Examples 1 to 13 were mixed in a mass percentage of 91:3:6, and the mixture was adjusted to a solid content of 50% with deionized water, and coated on both sides of the copper foil current collector, dried, and rolled to a surface density of 150 g / m 2 , a negative electrode sheet is obtained;

[0240] 1M sodium hexafluorophosphate was dispersed in an organic solvent of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1 (volume ratio) to prepare an electrolyte, and the positive and negative electrodes were assembled into a 554065 type soft pack battery according to an excess NP ratio of 20%, a PP separator and an electrolyte, and the test voltage range was 2V-4V;

[0241] 6C / 0.2C rate charge retention rate (%) test: At room temperature, the divided battery was subjected to constant current charge and discharge tests at 0.2C / 0.2C and 6C / 6C respectively. The 6C charge capacity was divided by the 0.2C charge capacity to obtain the 6C / 0.2C rate charge retention rate.

[0242] 1C / 1C cycle 500-week retention rate (%) test: At room temperature, a 1C / 1C constant current charge and discharge cycle test was performed. The discharge capacity of the 500th week was divided by the discharge capacity of the first week to obtain the 1C / 1C cycle 500-week retention rate.

[0243] The test results are shown in Table 1 and Table 2:

[0244] Table 1

[0245]

[0246]

[0247] Table 2

[0248]

[0249]

[0250] As shown in Table 1, Table 2, Figure 2 , Figure 3 and Figure 4 As shown, the specific capacity of the sodium ion battery containing the electrode materials of Examples 1 to 19 is 254.5mAh / g-451.1mAh / g, the first efficiency is 84.4%-93.8%, the 6C / 0.2C charging capacity retention rate is as high as 73.1%-93.1%, and the room temperature 1C / 1C@500 cycle retention rate is 73.5%-97.2%. The sodium ion battery containing the electrode materials of Examples 1 to 10 has good electrochemical properties, which shows that the electrode material provided by the present invention has the advantages of high capacity, high first efficiency, high rate and long cycle. This is because the electrode material provided by the present invention, through pore-forming treatment, metal salt solution impregnation, secondary conversion (metal salt is converted into metal oxide at high temperature, and metal oxide is converted into metal nitride under the action of process gas) and other processes, realizes the nano-metal nitride and uniformly loads it on the surface and pores of the carbon matrix, improves the electronic conductivity and pore volume of the carbon matrix surface and pore area, and provides a prerequisite for improving the pore sodium storage activity of the electrode material. In addition, a high-temperature sintering process is used to transform the open pores of the carbon matrix into closed pores with sodium storage activity, and it is beneficial to fix the metal nitrides in the closed pores, thereby improving the activity of pore sodium storage and the sodium storage utilization rate of the carbon matrix pore volume, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0251] From the analysis of Examples 1-19 and Comparative Examples 1 and 4, it can be seen that the pore-forming treatment of the pre-carbonized material can increase the particle porosity and pore sodium storage sites of the electrode material, provide a structural basis for improving the pore sodium storage activity of the electrode material, and is beneficial to the subsequent formation of closed pores and the fixation of metal nitrides in the closed pores; in addition, the total content of metal nitrides in Examples 1 to 19 is relatively high, which is also beneficial to improving the rate performance and cycle performance of the electrode material.

[0252] From the analysis of Example 1, Example 2, Example 5, Example 11 and Example 12, it can be seen that controlling the mass ratio of the pre-carbonized material and the solid-phase pore-forming agent within an appropriate range is conducive to the formation of closed pores, ensuring that the electrode material has a suitable particle porosity, increasing the content of metal nitride in the electrode material, and further improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0253] Analysis of Example 1 and Example 13 shows that purification of the pore-forming modified material can further improve the sodium storage capacity, rate performance and cycle performance of the electrode material. The purification treatment can remove the residual pore-forming agent or impurities in the pore-forming modified material, reduce the side reactions of the residual pore-forming agent and impurities during the battery charging and discharging process, and at the same time, prevent the residual pore-forming agent and impurities from occupying the pore volume of the first precursor, increase the loaded metal nitride content of the electrode material, and further ensure that the electrode material has good sodium storage capacity, rate performance and cycle performance.

[0254] Analysis of Example 6 and Example 7 shows that evenly mixing the coated carbon source with the second precursor and then sintering at high temperature can increase the content of metal nitride in the closed pores, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material. The coated carbon source can promote the conversion of open pores into closed pores, restrict the escape of metal nitrides from the pores, effectively fix the metal nitride in the pore structure, and increase the pore sodium storage site, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0255] From the analysis of Examples 1-19, Comparative Examples 3 and 4, it can be seen that reacting the intermediate with the process gas at high temperature is beneficial to converting the metal salt into metal nitride, increasing the content of metal nitride in the electrode material, and improving the electronic conductivity of the carbon matrix surface and pore areas, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0256] From the analysis of Example 1, Example 2, Example 5, Example 14 and Example 15, it can be seen that when the intermediate reacts with the process gas at high temperature, controlling the reaction temperature within an appropriate range is conducive to increasing the content of metal nitride in the electrode material, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material. Controlling the reaction temperature within an appropriate range can increase the conversion rate of metal nitride, reduce the sublimation of metal nitride, and thus increase the content of metal nitride in the electrode material.

[0257] Analysis of Example 6 and Example 8 shows that the use of process gases containing carbon atoms and amino groups can increase the content of metal nitrides in closed pores, thereby improving the sodium storage capacity, rate performance and cycle performance of electrode materials. The process gas containing carbon atoms and amino groups can produce ammonia, which can react with metal oxides at high temperatures to form metal nitrides. At the same time, the process gas contains carbon atoms, which can be used as a coating carbon source to carbon-coat the intermediate, reduce the pore size of the intermediate opening, and is conducive to the formation of closed pores, inhibiting the generated metal nitride from escaping from the pore structure, and ensuring the effectiveness of the metal nitride modification of the closed pores.

[0258] From the analysis of Example 1, Example 2, Example 16 and Example 17, it can be known that when the second precursor is subjected to high-temperature sintering, the temperature of the high-temperature sintering is controlled within an appropriate range, which can further ensure the sodium storage capacity, rate performance and cycle performance of the electrode material. Controlling the temperature of the high-temperature sintering within an appropriate range can promote the effective conversion of open pores into closed pores, and at the same time, reduce the collapse or partial collapse of closed pores, thereby increasing the particle porosity and closed pore volume of the electrode material; in addition, controlling the temperature of the high-temperature sintering within an appropriate range can reduce the sublimation of metal nitrides, which is beneficial to increase the content of metal nitrides in the electrode material, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0259] Analysis of Examples 1-19 and Comparative Example 2 shows that Examples 1-19 have higher sodium storage capacity, rate performance and cycle performance. The reason may be that the intermediate of Comparative Example 2 is not immersed in a metal salt solution, and metal nitrides cannot be formed in the electrode material; while metal nitrides are formed in the electrode materials of Examples 1-19, and metal nitrides have higher electronic conductivity characteristics, which can increase the overall electronic conductivity of the electrode material and the utilization rate of sodium storage in the central area of ​​the closed pores, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0260] From the analysis of Example 2, Example 10, Example 18 and Example 19, it can be seen that controlling the concentration of the metal salt solution and the mass ratio between the intermediate and the metal salt solution within an appropriate range can further ensure the content of metal nitride in the electrode material and the particle porosity of the electrode material, thereby improving the sodium storage capacity, rate performance and cycle performance of the electrode material.

[0261] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. An electrode material, characterized in that: include a carbon matrix having closed pores; A metal nitride, wherein the metal nitride is doped in the carbon matrix; Wherein, at least part of the metal nitride is located in the closed pores.

2. The electrode material according to claim 1, characterized in that The metal nitride includes any one or more of iron nitride, cobalt nitride, nickel nitride, copper nitride, vanadium nitride, titanium nitride, manganese nitride and zirconium nitride; and / or The mass percentage of the metal nitride in the closed pores in the electrode material is 0.35%-2.2%; and / or The total content of the metal nitride in the electrode material is 0.5%-3.0% by mass; and / or The particle size of the metal nitride is less than 1 μm; preferably, the particle size of the metal nitride is less than 500 nm; further preferably, the particle size of the metal nitride is less than 100 nm; and / or At least part of the metal nitride is doped on the surface of the carbon matrix; and / or The carbon matrix includes porous hard carbon and a carbon coating layer coated on the surface of the porous hard carbon.

3. The electrode material according to claim 1 or 2, characterized in that The particle porosity of the electrode material is 5%-35%, preferably, the particle porosity is 10%-25%; and / or The conductivity of the electrode material is 40S / cm-70S / cm; preferably, the conductivity is 46S / cm-65S / cm; further preferably, the conductivity is 50S / cm-60S / cm; and / or The carbon interlayer spacing of the electrode material is 0.37nm-0.39nm; and / or The median particle size of the electrode material is 3 μm-15 μm; and / or The specific surface area of ​​the electrode material is 2.0 m 2 / g-10.0m 2 / g.

4. A method for preparing an electrode material, characterized in that: The steps include: Pre-carbonizing the carbon source to obtain a pre-carbonized material; Performing pore-forming treatment on the pre-carbonized material and crushing it to obtain a first precursor; impregnating the first precursor in a metal salt solution to obtain an intermediate; reacting the intermediate with a process gas at a high temperature to obtain a second precursor; Sintering the second precursor at high temperature to obtain the electrode material; Wherein, the electrode material comprises: a carbon matrix having closed pores; A metal nitride, wherein the metal nitride is doped in the carbon matrix; The closed pores are filled with the metal nitride.

5. The preparation method according to claim 4, characterized in that: The carbon source includes any one or more combinations of plant carbon sources, sugar carbon sources, resin carbon sources, and polymer carbon sources; and / or The temperature of the pre-carbonization treatment is 450°C-650°C; and / or The pre-carbonization treatment time is 0.5h-24h; and / or The pre-carbonization treatment is carried out in an inert gas atmosphere or an oxygen-deficient atmosphere, wherein the inert gas atmosphere includes any one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere or a krypton atmosphere or a combination of at least two thereof, and the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content ≤1wt%.

6. The preparation method according to claim 4 or 5, characterized in that: The pulverizing includes: pulverizing the product of the pore-forming treatment to a median particle size of 3 μm-15 μm, and / or the pulverizing treatment includes a combination of one or more of ball milling, air flow pulverizing, mechanical pulverizing, and roller pressing pulverizing; and / or The pore-forming treatment includes solid-phase pore-forming, and the solid-phase pore-forming includes the following steps: under inert atmosphere conditions, the pre-carbonized material is uniformly mixed with a solid-phase pore-forming agent, and subjected to high-temperature treatment to obtain a solid-phase pore-forming modified material; and / or The pore-forming treatment includes gas-phase pore-forming, which includes the following steps: placing the pre-carbonized material in a reaction furnace, introducing a pore-forming gas, heating it to a first temperature and then maintaining the temperature to obtain a gas-phase pore-forming modified material.

7. The preparation method according to claim 6, characterized in that: In the solid phase pore formation, the temperature of the high temperature treatment is 600° C.-800° C., and the time of the high temperature treatment is 0.5 h-8 h; and / or The mass ratio of the pre-carbonized material to the solid phase pore forming agent is 1:(0.4-3.0); and / or The solid phase pore forming agent comprises at least one of sodium hydroxide, potassium hydroxide, sodium oxide, potassium oxide, sodium carbonate, potassium carbonate, potassium bicarbonate, sodium bicarbonate, calcium oxide and zinc chloride; and / or In the solid phase pore formation, the inert atmosphere includes any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two thereof; and / or The solid-phase pore-forming treatment also includes a solid-phase pore-forming modified material purification treatment, which includes: mixing the solid-phase pore-forming modified material, acid solution, and pure water in a mass ratio of 1: (0.5-2): (2-5) and stirring for 0.5h-24h, performing solid-liquid separation after the stirring is completed, washing the purified product obtained by solid-liquid separation to a pH of 2.5-4.5, and drying, wherein the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid; and / or In the gas phase pore formation, the first temperature is 800° C.-1000° C., and the insulation time is 1 h-8 h; and / or The pore-forming gas includes any one of water vapor, carbon dioxide, chlorine, oxygen, ozone, and air, or a combination of at least two thereof; and / or The gas-phase pore-forming treatment also includes a gas-phase pore-forming modified material purification treatment, which includes: mixing the gas-phase pore-forming modified material, acid solution, and pure water according to 1: (0.5-2): (1.2-5) and stirring for 0.5h-24h, performing solid-liquid separation after stirring, washing the purified product obtained by solid-liquid separation to a pH of 4-8, and drying; the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid.

8. The preparation method according to claim 4 or 5, characterized in that: The step of immersing the first precursor in a metal salt solution to obtain an intermediate specifically includes: The first precursor is immersed in the metal salt solution, stirred for 3h-24h, separated from the solid and liquid, and dried to obtain the intermediate.

9. The preparation method according to claim 8, characterized in that: The concentration of the metal salt solution is 0.5wt%-5wt%, and the mass ratio of the first precursor to the metal salt solution is 1:(3-20); and / or The median particle size of the first precursor is 3 μm-15 μm; and / or The metal salt includes a soluble salt of Co, Ni, Cu, V, Ti, Mn, Fe or Zr, and the soluble salt includes one or a combination of at least two of sulfate, nitrate and chloride.

10. The preparation method according to claim 4 or 5, characterized in that: The step of reacting the intermediate with a process gas at a high temperature to obtain a second precursor specifically includes: Under inert atmosphere conditions, the intermediate is placed in a reaction furnace, a process gas is introduced, the temperature is raised to a second temperature, the temperature is maintained, and the second precursor is obtained by cooling.

11. The preparation method according to claim 10, characterized in that: The second temperature is 1000° C.-1400° C., and the insulation time is 3 h-10 h; and / or The process gas is one of ammonia, methylamine, ethylamine, diethylamine, n-propylamine, isopropylamine, or a combination of at least two of them. Preferably, the selected process gas includes at least one of methylamine, ethylamine, diethylamine, n-propylamine, and isopropylamine; and / or The inert atmosphere includes any one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere or a krypton atmosphere, or a combination of at least two of them.

12. The preparation method according to claim 4 or 5, characterized in that: In the step of sintering the second precursor at high temperature to obtain the electrode material, the high temperature sintering is performed under inert atmosphere conditions, and / or the high temperature sintering temperature is 1200° C.-1500° C., and the high temperature sintering time is 0.5 h-10 h; and / or Before the second precursor is subjected to high temperature sintering, the method further includes the following steps: uniformly mixing the coated carbon source and the second precursor.

13. The preparation method according to claim 12, characterized in that: The mass ratio between the second precursor and the coated carbon source is 1:(0.01-0.1); and / or The coated carbon source comprises any one or more combinations of asphalt, sucrose, phenolic resin, polyacrylic resin, glucose, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyvinyl alcohol, epoxy resin, urea-formaldehyde resin, and melamine resin; and / or The inert atmosphere is any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two of them.

14. An electrode plate, characterized in that: The invention comprises the electrode material according to any one of claims 1 to 3 or the electrode material prepared by the preparation method according to any one of claims 4 to 13.

15. A sodium ion battery, characterized in that: The invention comprises the electrode material according to any one of claims 1 to 3 or the electrode material prepared by the preparation method according to any one of claims 4 to 13.

Citation Information

Patent Citations

  • Preparation method of three-dimensional porous Fe3N / carbon composite material for sodium electricity

    CN115159476A

  • Composite hard carbon material and preparation method and application thereof

    CN115911320A

  • Preparation method of bamboo hard charcoal material and bamboo hard charcoal material

    CN117602610A

  • Method for preparing hard carbon negative electrode material rich in closed pores from porous carbon and application of hard carbon negative electrode material

    CN118239487A

  • Sodium-ion battery negative electrode biomass hard carbon material, preparation method and sodium-ion battery

    CN118529711A

Cited By

  • Solid particle volatilization pore-forming type sodium electric dry method positive plate as well as preparation method and application thereof

    CN121812601A

  • Solid particle volatilization pore-forming type sodium battery positive electrode sheet and preparation method and application thereof

    CN121812601B